Yield Regulation in the High Forests of Bihar - Mishra, P. (Indian Forester, 1962)
The development of the scientific management of forests in Bihar has been traced. Yield was used to be fixed arbitrarily till Haines wrote the first regular Working Plan in 1903-04, and introduced Selection felling. With the introduction of the Conversion to Uniform System in Porahat, Saraods and Kolhao, the yield in Periodic Block I was generally fixed by volume expressed in terms of unit values and Selection felling. Were prescribed in the other Periodic Blocks and in the Hill Working Circle. Smythies’ safeguarding formula was first adopted in the State in Derry’s plan for Porahat. Past-war years have seen the evolution of the technique of partial sampling enumeration. Startlng from completely randomized design in Palaman, the stratification has been taken to a Compartment or a group of Compartments in Saranda and Kolban. It is suggested that stratum design based on considerations of geology, topography and aspect should appreciably increase the precision of the estimates. Laying out of increment plots, both linear or of irregular sizes has been suggested not only to find out the response of the forest to the prescribed treatment but also to fix the correct values of Smythies’ Constants. It has also been suggested that the yield might be fixed separately for ddferent Compartments or a set of homogeneous compartments even in the same felling series.